2010
DOI: 10.1038/nri2836
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral immune responses in the genital tract: clues for vaccines

Abstract: Mucosal surfaces are often exploited as a portal of entry by a wide variety of microorganisms. An advanced understanding has been gained over the past decade of the immune system of the gastrointestinal and the respiratory mucosae. However, despite the fact that many viruses are transmitted sexually through the genital tract, the immune system of the male and female genital mucosae has received much less attention. Here, I describe and highlight differences of the innate and adaptive immune systems of the geni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
151
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(156 citation statements)
references
References 132 publications
(123 reference statements)
5
151
0
Order By: Relevance
“…Animal studies have also demonstrated that TRMs mediate local protection against genital HSV‐2 infections (Shin, Kumamoto, Gopinath & Iwasaki, 2016). Therefore, induced immune cell protection against STIs in humans would likely require a potent resident memory T‐cell population (Iwasaki, 2010). Based on our findings, we speculate that despite vaccination, TRMs will not be equally induced and distributed throughout the FRT and will differ depending on women's age.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have also demonstrated that TRMs mediate local protection against genital HSV‐2 infections (Shin, Kumamoto, Gopinath & Iwasaki, 2016). Therefore, induced immune cell protection against STIs in humans would likely require a potent resident memory T‐cell population (Iwasaki, 2010). Based on our findings, we speculate that despite vaccination, TRMs will not be equally induced and distributed throughout the FRT and will differ depending on women's age.…”
Section: Discussionmentioning
confidence: 99%
“…This virus produces a lytic infection of epithelial cells in the skin and then spreads to nearby neurons, where it can persist for the life of the host (162). Local dendritic cells are also infected, at least early on (163)(164)(165)(166)(167).…”
Section: Srivastava and Ernst Recently Shed Light On How The Interactmentioning
confidence: 99%
“…Local dendritic cells are also infected, at least early on (163)(164)(165)(166)(167). T cells are thought to play a role in keeping the infection in a latent state in neurons, although this state can sporadically break down, resulting in viral replication and a skin lesion (162). CD8 ϩ T cells likely contribute to the control of infection by killing epithelial cells that become infected after the virus emerges from persistently infected neurons (162).…”
Section: Srivastava and Ernst Recently Shed Light On How The Interactmentioning
confidence: 99%
“…As with other barrier surfaces, commensal microbiota, largely of the Lactobacillus species, shape the microenvironment of the vaginal tract. Lactobacilli produce hydrogen peroxide to prevent the outgrowth of harmful bacteria, and maintain the acidic pH of the vaginal mucosa through lactic acid production, which provides resistance against pathogens (9). Imbalances in the vaginal flora, called dysbiosis, result in outgrowth of pathogenic bacteria; however, the consequence of dysbiosis on genital antiviral immunity remains to be elucidated.…”
mentioning
confidence: 99%